1987
DOI: 10.1002/jhrc.1240100510
|View full text |Cite
|
Sign up to set email alerts
|

High oven temperature — cold on‐column injection for the automated CGC analysis of high molecular weight compounds such as triglycerides

Abstract: Modification of the Carlo-Erba cold on-column injector for (automated) analysis of high molecular compounds at high oven temperatures is described. The secondary cooling tube of the cold on-column injector is replaced by a lengthened tube through which a high air flow is directed. The injection site is maintained at 65-70°C while the oven is at high temperature (Z 3OOOC). For automated injection, a short deactivated precolumn of 22 to 30 cm X 0.53 mm i.d. is coupled to the analytical column via a butt connecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Geeraert and Sandra [45] stated that the response factors for TGs, except for highly unsaturated substances, are almost equal to one by using OCI and a 25-m polarisable capillary column, and that no special attention need to be paid to this subject, whereas Termonia and co-workers [42] reported that a higher bleeding level of phenylmethylsilicone phases resulted in lower response factors. This is quite in contrast with another report, where recovery of triolein (OOO), trilinolein (LLL) and trilinolein (LnLnLn) from a 25-m medium polarity capillary column dropped to 94%, (OOO), 70% (LLL) and 35% (LnLnLn), assuming that tristearin was recovered to 100% [80].…”
Section: Gas Liquid Chromatographymentioning
confidence: 97%
See 2 more Smart Citations
“…Geeraert and Sandra [45] stated that the response factors for TGs, except for highly unsaturated substances, are almost equal to one by using OCI and a 25-m polarisable capillary column, and that no special attention need to be paid to this subject, whereas Termonia and co-workers [42] reported that a higher bleeding level of phenylmethylsilicone phases resulted in lower response factors. This is quite in contrast with another report, where recovery of triolein (OOO), trilinolein (LLL) and trilinolein (LnLnLn) from a 25-m medium polarity capillary column dropped to 94%, (OOO), 70% (LLL) and 35% (LnLnLn), assuming that tristearin was recovered to 100% [80].…”
Section: Gas Liquid Chromatographymentioning
confidence: 97%
“…The injection technique has been considered as being most critical for obtaining high accuracy and precision, since at this stage discrimination against less volatile high molecular weight compounds can occur while the sample is being transferred from the syringe to the column (syringe discrimination) [71,72]. Many authors [32,40,42,72,73] published detailed studies concerning the effect of the injection technique on the recovery of TGs.…”
Section: Gas Liquid Chromatographymentioning
confidence: 98%
See 1 more Smart Citation
“…Com o desenvolvimento das colunas capilares, várias publicações demonstraram a aplicabilidade da CGAR e CGAR-AT, para a caracterização de óleos e gorduras, com resolução suficiente para diferenciar os diferentes triglicerídeos insaturados [76][77][78][79] . Esta técnica analítica foi desenvolvida principalmente para caracterização de adulterações de óleos utilizados na indústria alimentícia devido a fatores econômicos, como por exemplo, a adulteração intencional de azeite de oliva por adição de óleo de soja (que possui um menor valor agregado) 80 .…”
Section: Triglicerídeosunclassified
“…As such, HT-HRGC may be an excellent alternative to classical analytical phytochemistry and a potent tool for the study of medicinal plants. HT-HRGC has been already reported in the analysis of high molecular weight compounds as, for example: porphyrins [16], cyclodextrin derivatives [17 -18], HMW n-alkanes [19], triglycerides [20], oligossaccharides [21], lipids [22], in widely different matrices, including, recently, environmental samples [23 -25].…”
Section: Introductionmentioning
confidence: 99%